Asia : displacing Europe as a centre of defence innovation? - Bitzinger, Richard A. (2015)
Europe’s relative decline as a military-technological power has provided an opportunity for Asian-Pacific powers to rise in its stead. Europe’s military-technological establishment could recover, but it requires significant additional funding and a renewed commitment to international arms collaboration that currently does not exist.